2019
DOI: 10.3393/ac.2019.10.21
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Colorectal Cancer in Korea: A Population-Based Retrospective Cohort Study

Abstract: The incidence of colorectal cancer in Korea has recently increased, making it the second most common cancer in men and the third most common cancer in women. Risk factors for colorectal cancer have been studied worldwide, but risk factors specific for the Korean population have not been established. In this study, we investigated incidence trends and risk factors of colorectal cancer in Korea. Methods: A total of 8,846,749 subjects were included. Colorectal cancer incidence was investigated using Korea Nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 42 publications
3
29
0
Order By: Relevance
“…The incidence of nonadenocarcinoma in Korea was much lower than that of adenocarcinoma. The age-standardized incidence rates of colon adenocarcinoma in 2014 were 64.8 per 100,000 in men and 44.0 in women [13]. We also found that nonadenocarcinoma was relatively more frequent among younger patients than adenocarcinoma.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The incidence of nonadenocarcinoma in Korea was much lower than that of adenocarcinoma. The age-standardized incidence rates of colon adenocarcinoma in 2014 were 64.8 per 100,000 in men and 44.0 in women [13]. We also found that nonadenocarcinoma was relatively more frequent among younger patients than adenocarcinoma.…”
Section: Discussionsupporting
confidence: 56%
“…We also found that nonadenocarcinoma was relatively more frequent among younger patients than adenocarcinoma. The frequency of adenocarcinoma increases rapidly among patients in their 60s and is the highest among patients in their 60s, 70s, and 80s [13]. There has been little examination of the incidence and characteristics of colorectal nonadenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The age-standardized incidence rates of colon adenocarcinoma in 2014 were 64.8 per 100,000 in men and 44.0 in women. [13] We also found that non-adenocarcinoma was relatively more frequent among younger patients than adenocarcinoma. The frequency of adenocarcinoma increases rapidly among patients in their 60s and is the highest among patients in their 60s, 70s, and 80s.…”
Section: A C C E P T E D a R T I C L Esupporting
confidence: 52%
“…Colorectal cancer (CRC) is the third most commonly diagnosed cancer worldwide and one of the leading causes of cancer-specific death [9], with more than 1.1 million cancer deaths expected by 2030 [10]. According to the published studies, diet [11], obesity [12], alcohol intake [13] and diabetes [14] are all risk factors for the occurrence and mortality in patients with CRC. Since 2001, several epidemiological studies have investigated the association between MetS and CRC risk but showed inconsistent results.…”
Section: Ivyspringmentioning
confidence: 99%